Computational Modelling of Blood Flow Development and Its Characteristics in Magnetic Environment. (11th November 2013) - Shit, Gopal Chandra
Abstract : Of concern in this paper is an investigation of the entrance length behind singularities in cardiovascular hemodynamics under magnetic environment. In order to get better interpretation of scan MRI images, the characteristics of blood flow and electromagnetic field within the circulatory system have to be furthermore investigated. A 3D numerical model has been developed as an example of blood flowing through a straight circular tube. The governing coupled nonlinear differential equations of magnetohydrodynamic (MHD) fluid flow are reduced to a nondimensional form, which are then characterized by four dimensionless parameters. With an aim to validate our numerical approach, the computational results are compared with those of the analytical solution available in the developed region far from the singularity. The hydraulic impedance by unit length within the developed flow region increases with the magnetic field. The time average entrance length with a greater precision on the unsteady case decreases with increasing magnetic field strength. The overall voltage characteristics do not depend on the developed flow field within the entry region.